The Practice of Formation of Programs and Curricula for Advanced Training Courses for Teachers - Mykola Solovei (Pedagogical Discourse, 2017)
The article analyzes the practice of the Khmelnytskyi regional institute of postgraduate pedagogical education in terms of forming the curricula of advanced training courses (2010-2015).The basis for the development are qualification characteristics. In accordance with their structure, we design the main directions of programs and their components: social, humanitarian, psychological and methodological. Each component has a dynamic knowledge system in accordance with the content of core competencies. On their basis, we develop programs, training courses, trainings and seminars. Their relevance is determined by the trends in state educational policy and the level of development of science. Next, we form a general curriculum. The curriculum has a modular structure and is designed for 216 (144 academic) hours or 6 (six) credits.The curricula are differentiated: for specialists, specialists in the second, first and higher categories. Developed programs for distance learning and special courses for teachers who teach two or more subjects.Programs and curricula consist of four modules: humanitarian, psycho-pedagogical, special (methodical) and diagnostic. The humanitarian module includes issues of philosophy, law and the sociology of education. The psychological and pedagogical module includes questions of pedagogical innovation and age psychology. The module of special preparation corresponds to a certain branch of knowledge and methods of teaching the academic disciplines at school. More than 70 modules have been developed, which include directions: pre-school and primary education, as well as methods for studying literature, languages, history, mathematics, physics, chemistry, biology and other disciplines. The diagnostic module includes questions concerning the study of the level of preparation of the listener.Based on the general curriculum and structure of the courses, we develop a working curriculum. The work plan lists the number of lectures, seminars, practical, as well as the number of hours for independent study of disciplines and additional hours. The number of hours of the curriculum increases due to the division of groups, the verification of independent work, projects, coursework, etc.The working curriculum serves as the basis for the development of a common balance of hours, individual plans and training loads of teachers, budget courses, the wage fund.Programs and curricula are considered by us as a necessary internal standard for advanced training coursesIn the process of analyzing the work of the Institute, it is established that the preparation of programs and curricula is a long process. In their development, employees of departments, methodologists and teachers of schools are engaged. The cycle of works includes: preparation of qualifying characteristics, construction of substantial lines of programs, curricula and their variations.